The Gift of Knowledge / Ttnúwit Átawish Nch'inch'imamí : Reflections on Sahaptin Ways - Beavert, Virginia (Book collections on Project MUSE.)
"The Gift of Knowledge / Ttnuwit Atawish Nch'inch'imamí is a treasure trove of material for those interested in Native American culture. Author Virginia Beavert grew up in a traditional, Indian-speaking household. Both her parents and her maternal grandmother were shamans, and her childhood was populated by people who spoke tribal dialects and languages: Nez Perce, Umatilla, Klikatat, and Yakima Ichishkíin. Her work on Native languages began at age twelve, when she met linguist Melville Jacobs while working for his student, Margaret Kendell. When Jacobs realized that Beavert was a fluent speaker of the Klikatat language, he taught her to read and write the orthography he had developed to record Klikatat myths. After a stint in the U.S. Air Force during World War II, Beavert went on to earn graduate degrees in education and linguistics, and she has contributed to numerous projects for the preservation of Native language and teachings. Beavert narrates highlights from her own life and presents cultural teachings, oral history, and stories (many in bilingual Ishishkíin-English format) about family life, religion, ceremonies, food gathering, and other aspects of traditional culture."--Provided by publisher.